Jebakan Paternalistik Perempuan Nahdlatul Ulama Dalam Kancah Perpolitikan Nasional - FN, Ainna Amalia (Tribakti: Jurnal Pemikiran Keislaman, 2020)
Compared to previous years, women's participation in the political arena in the country in the last few years increased significantly. In the 2019 national elections, at the central level, 16 political parties had won a 30 percent quota for women candidates. This is certainly our appreciation, although the representation of women's representation at the provincial and district/city levels is still far from ideal. Likewise with the participation of female representatives from Nahdlatul Ulama. The results of the 2019 elections were quite significant changes, both representative from Fatayat and Muslimat. However, this significant increase in terms of numbers left a trap that seemed to entwine other NU women in the arena of national politics. Many NU women who opposed and issued him out of the ordinary, even raised in the discussion room, were unable to NU politics that adopted a system of the breed, dynasty, and over budgeting. Successful NU women "have no clear breed" have to settle for playing in the periphery of political space.